Kontribusi Pembiayaan Bank Syariah untuk Sektor Pertanian di Indonesia - Minhatul Mughits; Ries Wulandari (Department of Islamic Economics, IPB University, 2016)
Based on Islamic Banking Law Article 1 paragraph 2 funding was the main activity for Islamic banking in its function as a financial intermediary and drived real sector. This study was aim to determine how much the influences of SBIS, amount of DPK, Non Performing Financing and the exchange rate of dollar against the Islamic banking financing as well as the contribution of Islamic bank financing for the agricultural sector in Indonesia by using VAR/VECM approach. VECM results indicated variables that affected agricultural financing in the short term was variable LNER and SBIS. While in the long term variable lnDPK and lnNPF statistically significant against to agricultural financing. The results of IRF showed that lnDPK, lnNPF and LNER responded positively influencing the contribution of financing on Islamic bank for the agricultural sector in Indonesia. As for The contribution of financing on Islamic bank for the agricultural sector in Indonesia, LNER gave the largest contribution to the Islamic bank financing for the agricultural sector in Indonesia, followed by the variable SBIS, lnDPK, and lnNPF. The higher value of rupiah would increase the financing by the islamic banking for Agricultural sector, as would as the lower of rate SBIS would increase the financing of islamic banking.